Immobilization of lipases onto the SBA-15 mesoporous silica. Issue 3 (4th May 2017) - Gholamzadeh, Parisa; Mohammadi Ziarani, Ghodsi; Badiei, Alireza
Abstract: Lipase is an important enzyme which can catalyse the hydrolysis of lipids and has several applications and industrial potentials. In addition, different types of lipases are used as efficient catalysts in the enantioselective esterification and/or hydrolysis reactions and produce products in high yields and enantio excess as well. However, immobilization of lipases on the surface of a heterogeneous substrate is necessary to improve its specific catalytic activities as it can be isolated from the reaction mixture easily. Mesoporous silica materials are the best option for this aim due to their high specific surface area, ordered structure, and large pore volume. Hence, in this article, the role of SBA-15 and the modified SBA-15 mesoporous materials as support for different lipases and their catalytic activities are reviewed.